Development of a Propulsion System for a Maneuvering Module of a Low-orbit Nanosatellite. (2017) - Belokonov, Igor; Ivliev, Alexander
Abstract: Nanosatellites (NS) are one of the fastest growing branches of spacecraft technologies. One of the attractive areas of application for such spacecraft is real-time low-orbit remote sensing of the Earth. This paper aims to develop a concept of a propulsion system (PS) and a maneuvering module (MM) for a CubeSat3U format low-orbit nanosatellite (NS), that would enable such spacecraft to maintain the required orbit altitude for a few weeks or months depending on insertion parameters. Requirements for the maneuvering module are stated. Helium, nitrogen and liquefied propane are considered as propellants. Modeling showed that helium provides the greatest specific impulse, but its density is too low to store a sufficient quantity. Under specified conditions, nitrogen may be able to provide required characteristics of the maneuvering module; specific impulse can be nearly doubled by heating the propellant to 700 °C with electric heaters.